Types of chicaneries regarding murabaha contracts in Islamic banks an analytical study صور الحيل في عقود المرابحة في المصارف الإسلامية دراسة تحليلية. - Saleh, Abdulmajid Obaid Hasan; Othman, Anwar Hasan Abdullah; Kaba, Abdol Razzak (2019)
Due to the importance of the Murabaha contract, and its adoption by many Islamic banks as a result of low risk product, to the extent that the use of the Murabaha formula in some banks represents 80% of the total financing operations, and because this contract contains a variety of procedures starting with the purchase order, and closing by finalizing the Murabahah contract between the bank (buyer) and the client (purchase orderer) by setting up the premium payment agreement, many of the violations, and some types of the chicaneries, which may occur in collusion of the bank, and sometimes can be ascribed to the misconducts of some staffs contrary to the general policy of the bank, and there are part of the chicaneries attributed to the client, all these need to be highlighted, analyzed and their legitimacy form Shariah point of view must be clarified. We have been keen to absorb most of the current chicaneries mentioned by contemporary fatwas, recent academic research papers, and reports of the relevant banks, we have adopted the descriptive and analytical approach in the study, aiming to a new and quality study as specialized value added in this field.